Respuesta :
Answer:
y = - 8x² + 6
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Here (h, k) = (0, 6), thus
y = a(x - 0)² + 6, that is
y = ax² + 6
To find a substitute (- 1, - 2) into the equation
- 2 = a(- 1)² + 6, that is
- 2 = a + 6 ( subtract 6 from both sides )
- 8 = a
y = - 8x² + 6
The formula of the quadratic function is [tex]y = -8x^2 + 6[/tex]
A quadratic function is represented as:
[tex]y = a(x - h)^2 + k[/tex]
The vertex of the quadratic function is given as:
[tex](h,k) = (0,6)[/tex]
So, we have:
[tex]y = a(x - 0)^2 + 6[/tex]
This gives:
[tex]y = ax^2 + 6[/tex]
The quadratic function passes through (-1,-2).
So, we have:
[tex]-2 = a(-1)^2 + 6[/tex]
[tex]-2 = a + 6[/tex]
Subtract 6 from both sides
[tex]a = -8[/tex]
Substitute -8 for a in [tex]y = ax^2 + 6[/tex]
[tex]y = -8x^2 + 6[/tex]
Hence, the formula of the quadratic function is [tex]y = -8x^2 + 6[/tex]
Read more about quadratic functions at:
https://brainly.com/question/11631534